2020
DOI: 10.1108/aeat-08-2020-0181
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the potential of commercial use of microalgae in the world and in Ukraine

Abstract: Purpose This paper aims to evaluate of the microalgae potential for commercial application, in particular to conduct experimental study of biogenic compounds removal from sewage waters by microalgae, and to calculate economical benefits from biofertizers and biofuel production. Design/methodology/approach Experimental study in the concentration change of nitrogen and phosphorus compounds in the cultivation of Chlorella Vulgaris microalgae in various types of sewage water was carried out. Findings The effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…1. Euglena gracilis (HPDP-114) microalgae strain was experimentally cultivated in artificial sewage water with different concentrations of phosphates: 4, 7, and 14 mg/dm 3 . It was shown that phosphates were removed from sewage water (residual concentration: 0…0.55 mg/dm 3 ) during the cultivation period (four days).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…1. Euglena gracilis (HPDP-114) microalgae strain was experimentally cultivated in artificial sewage water with different concentrations of phosphates: 4, 7, and 14 mg/dm 3 . It was shown that phosphates were removed from sewage water (residual concentration: 0…0.55 mg/dm 3 ) during the cultivation period (four days).…”
Section: Discussionmentioning
confidence: 99%
“…The studied strain was obtained from the Bank of Microalgae Cultures of the Institute of Hydrobiology of the National Academy of Sciences of Ukraine. Artificial sewage water was prepared according to the recipe of biogenic culture medium containing 0.4 g/dm 3 magnesium sulfate solution (MgSO 4 ×7H 2 O); 0.05 g/dm 3 calcium chloride solution (CaCl 2 ×2H 2 O); 0.1 g/dm 3 sodium chloride (NaCl); 5 g/dm 3 glucose; 1 g/dm 3 α-glutamic acid; 1 g/dm 3 trace element solution; 1g/dm 3 ethylenediaminetetraacetic acid solution with iron ions (Fe-EDTA). To create a concentration of biogenic elements close to the concentration in real sewage water, potassium dihydro orthophosphate KH 2 PO 4, and ammonium chloride NH 4 Cl were added to the culture medium in different amounts to achieve different phosphorus concentrations.…”
Section: The Study Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations